Heavy Metal Contamination of Lead (Pb) In Local Food Bilvaves - nur hasanah (Media Gizi Kesmas, 2022)
Background: Bilvave is a potential biological food resource from water areas. Bilvave are one of the local food sources that are widely consumed by the community because of their affordable prices and high-quality alternative protein sources. Bilvave can accumulate various particles including heavy metals in water, one of which is lead. The presence of lead in food in high concentrations and in the long term can have an impact on the health of humans who consume it. Objectives: The purpose of this literature review is to describe the heavy metal content of lead in bilvave and the health effects of those who consume them. Methods: The method used in writing this literature review is to review 11 selected journals taken from various sources, namely Google Scholar, Crossref, Elsevier, Springer with open access journal criteria and according to the topic to be discussed. Discussion: The results of a review of several articles show that the lead content in bilvave exceeds the threshold for proper consumption based on the regulations regarding heavy metal contamination in food that have been determined. Conclusions: There are variations in the heavy metal content of lead in several types of shellfish that are often consumed by the public. This is influenced by the water area where the shells are obtained with different levels of water pollution, for that it is important for the public to pay attention to the frequency of consumption and how to process shellfish before consumption. Keywords: Heavy metal contamination, Lead and Shellfish